Enhancing TiO2 Photoelectrode Performance: The Role of La Doping Using the Sol-Gel Process - Jannah, Mifthahul; Azmi, Nurul; Lala, Andi; Jalil, Zulkarnain; Mursal, Mursal (Heca Journal of Applied Sciences, 2025)
Due to growing interest in renewable energy technologies, dye-sensitized solar cells (DSSCs) have emerged as promising alternatives to conventional photovoltaics. This study explores the enhancement of titanium dioxide (TiO2) photoelectrodes through doping with lanthanum (La), a rare earth element known for its ability to modify semiconductors' structural and electronic properties. La-doped TiO2 was synthesized using the sol-gel method with La concentrations ranging from 0 to 4 mol%. The resulting films were deposited onto substrates and sintered at 600 °C for 1 hour. Characterization techniques included X-ray diffraction (XRD), scanning electron microscopy with energy-dispersive spectroscopy (SEM-EDS), UV-Vis spectrophotometry, and Fourier-transform infrared spectroscopy (FTIR). XRD confirmed the anatase phase of TiO2 and the appearance of La2O₃ phases with doping. The smallest crystallite size (8.20 nm) and lowest bandgap energy (3.31 eV) were achieved at 1 mol% La, compared to 3.52 eV for undoped TiO2. SEM-EDS indicated uniform La distribution, while FTIR revealed changes in surface chemistry. These results suggest that La doping, particularly at 1 mol%, can effectively enhance the optical and structural properties of TiO2, making it a promising candidate for improved DSSC performance.